2017
DOI: 10.1175/waf-d-17-0037.1
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Tropical Cyclone Eye Formation and Dissipation in Infrared Imagery

Abstract: The development of an infrared (IR; specifically near 11 μm) eye probability forecast scheme for tropical cyclones is described. The scheme was developed from an eye detection algorithm that used a linear discriminant analysis technique to determine the probability of an eye existing in any given IR image given information about the storm center, motion, and latitude. Logistic regression is used for the model development and predictors were selected from routine information about the current storm (e.g., curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…It is also important to address whether logistic regression fits the data well. Following the introduction to percentage deviance explained by Knaff and DeMaria (2017), it was found that the maximum percentage deviance explained is 42.6 for TINT-RI specifically for the two shorter forecast lead-times. Percentage deviance explained decayed with the growth in lead-time and dropped to a minimum of 25.3 for +48 hr forecasts.…”
Section: Consensus Ri Probabilitymentioning
confidence: 99%
“…It is also important to address whether logistic regression fits the data well. Following the introduction to percentage deviance explained by Knaff and DeMaria (2017), it was found that the maximum percentage deviance explained is 42.6 for TINT-RI specifically for the two shorter forecast lead-times. Percentage deviance explained decayed with the growth in lead-time and dropped to a minimum of 25.3 for +48 hr forecasts.…”
Section: Consensus Ri Probabilitymentioning
confidence: 99%
“…A number of methods for detecting the center of a tropical cyclone have been developed in the past few decades, including wind field analysis [6] and pattern matching [7,8], which used a linear discriminant analysis technique to determine the probability of an eye existing in any given IR image. Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Such approaches discard complex, time-evolving structure in the 2D fields. More recent analyses take spatial information into account by applying dimension reduction techniques like functional principal component analysis (PCA) to the field, such as for TC eye formation forecasts in (Knaff and DeMaria, 2017). However, dimension reduction adds an extra layer of abstraction between TC structure and subsequent TC behavior and can reduce meteorologists' ability to interpret the information.…”
Section: Introductionmentioning
confidence: 99%